Coffee market price as a reflection of the brazilian harvest (Research, Society and Development, 2024)
Brazilian agribusiness has great importance in the constitution of national gross domestic product, reaching values of more than 27% representativeness. Within the agricultural products we have coffee as one of the great crops in our country. As it is known its market value fluctuates, like all products, by the most diverse factors. This work aimed to evaluate the existence or not of a correlation in the market price of coffee with production factors in Brazil. Variation along the years of Brazilian total coffee production, total area in production and area of crop formation was explored via a Pearson’s correlation analysis with significance of 95%. Pearson's correlation analysis identified a negative correlation of -0.33 between the negotiation price of the coffee sack (60 kg) and the total production volume of the Brazilian crop. Considering that the market value of this product can be affected by numerous factors we conclude the significant existence of this correlation.